Association between FTO polymorphism and COVID-19 mortality among older adults: A population-based cohort study - Hubacek, Jaroslav A; Capkova, Nadezda; Bobak, Martin; Pikhart, Hynek (International journal of infectious diseases, 2024)
OBJECTIVES: COVID-19 caused a global pandemic with millions of deaths. Fat mass and obesity-associated gene (FTO) (alias m6A RNA demethylase) and its functional rs17817449 polymorphism are candidates to influence COVID-19-associated mortality since methylation status of viral nucleic acids is an important factor influencing viral viability. METHODS: We tested a population-based cohort of 5233 subjects (aged 63-87 years in 2020) where 70 persons died from COVID-19 and 394 from other causes during the pandemic period. RESULTS: The frequency of GG homozygotes was higher among those who died from COVID-19 (34%) than among survivors (19%) or deaths from other causes (20%), P <0.005. After multiple adjustments, GG homozygotes had a higher risk of death from COVID-19 with odds ratio = 2.01 (95% confidence interval; 1.19-3.41, P <0.01) compared with carriers of at least one T allele. The FTO polymorphism was not associated with mortality from other causes. CONCLUSIONS: Our results suggest that FTO variability is a significant predictor of COVID-19-associated mortality in Caucasians.
Keywords: Alpha-Ketoglutarate-Dependent Dioxygenase FTO; senioři; lidé středního věku; Alleles; Polymorphism, Single Nucleotide; kohortové studie; genetická predispozice k nemoci; Female; Humans; COVID-19; Aged; Male; Cohort Studies; ženské pohlaví; Middle Aged; Genetic Predisposition to Disease; jednonukleotidový polymorfismus; alely; lidé; mužské pohlaví; gen pro FTO; senioři nad 80 let; SARS-CoV-2; Aged, 80 and over